HLA and ABO antigens in malignant choroidal melanoma. - Völker-Dieben, H J (1983)
Comparisons of the HLA antigen frequencies in normal controls and in different subsets of patients with malignant choroidal melanoma, partitioned on the basis of histological tumour cell types and inclusion of the splits of all the HLA-A and -B locus antigens, revealed significant heterogenity only in HLA-B (P = 0.043) in the 'pure spindle' cell type choroidal melanomas. In the 'not pure spindle' cell type choroidal melanomas, borderline heterogenity in HLA-B (P = 0.064) was observed. A comparison of the HLA antigen frequencies in the 'pure' and 'not pure spindle' cell choroidal melanoma patients revealed only one antigen with a significant difference before correction, namely B27. A significant difference in ABO bloodgroup distributions, divided into O and non-O, in the two tumour classes was observed (Exact P(1) = 0.0036).